The decisive role of the crystalline crust faults in the Black Sea opening - Rusakov, O.M.; Pashkevich, I.K. (Геофизический журнал, 2017)
The results of the international "Geology without Limits" project unequivocally confirmed the faults pattern in the crystalline crust of the Black Sea delineated from gravity and magnetic data. The locations of 135 from among ca. 150 faults on its surface derived from the seismic sections of this project completely coincide with those of the present study used. Результати міжнародного проекту .Геологія без кордонів. беззастережно підтвердили наявність системи розломів у кристалічній корі басейну Чорного моря, виділених за гравітаційними і магнітними даними. Місця розташування 135 з майже 150 розломів на її поверхні, отриманих за даними аналізу сейсмічних розрізів у рамках цього проекту, повністю збігаються з розломами виділеної системи.